Review: The Development of Risk Factors and Cytokines in Retinal Vein Occlusion - Tang, Yi; Cheng, Yan; Wang, Shuo; Wang, Yongjie; Liu, Pengjia; Wu, Hong (Frontiers in Medicine, 2022)
Retinal vein occlusion (RVO) is the second most prevalent retinal disease. Despite this, the pathogenic mechanisms and risk factors are not entirely clear. In this article, we review recent publications on the classification, pathogenesis, risk factors, ischemic changes, cytokines, and vital complications of RVO. Risk factors and cytokines are important for exploring the mechanisms and new treatment targets. Furthermore, risk factors are interrelated, making RVO mechanisms more complex. Cytokines act as powerful mediators of pathological conditions, such as inflammation, neovascularization, and macular edema. This review aims to summarize the updated knowledge on risk factors, cytokines of RVO and signaling in order to provide valuable insight on managing the disease.